Progress in quality assessment of Italian saffron - Irene Locatelli; Davide Pedrali; Silvia Grassi; Susanna Buratti; Annamaria Giorgi; Luca Giupponi (Scientific Reports)
Abstract Saffron (Crocus sativus L.) is the most expensive spice in the World, and Italy is among the major European producers. The study aims to improve value and recognition of high quality saffron by proposing a subdivision within the first quality category, according to ISO 3632 standards. The analysis of 125 saffron samples, collected from different Italian regions in 2021–2022 harvesting seasons, revealed that 95% of the samples met the first quality criteria, following ISO guidelines. Consequently, for the first quality samples, a differentiation into “premium”, “superior” and “high-quality” subcategories was proposed. Along with traditional methods, FT-NIR spectroscopy combined with chemometrics was employed for a comprehensive quality assessment. Discriminant and class-modelling approaches were developed to predict saffron quality subcategory. Best results were obtained by linear discriminant analysis models with accuracy in calibration (92.7%), cross-validation (86.4%) and prediction (87.0%). However, SIMCA modelling resulted more appropriate for class-modelling, confirming that none of the “premium” samples were misclassified as “high-quality” and vice-versa. The results support the inclusion of subcategories within ISO 3632 standards, thus refining the classification of saffron quality. Furthermore, the study emphasises the effectiveness of FT-NIR spectroscopy as a valuable tool for saffron quality assessment, with potential implications for industry standards and practices.